2020
DOI: 10.1177/1533033820980113
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of L-asp Activity, Anti-L-asp Antibody, Asn and Gln With Adverse Events Especially Anaphylaxis Risks in PEG-asp-Contained Regime Treated Pediatric ALL Patients

Abstract: Objective: This study aimed to investigate the correlation of L-asparaginase (L-asp) activity, anti-L-asp antibody, asparagine and glutamine levels with the risks of adverse events (AEs), especially anaphylaxis, in pediatric acute lymphoblastic leukemia (ALL) patients who underwent polyethylene glycol-conjugated L-asp (PEG-asp)-contained treatment. Methods: Plasma samples were collected from 91 pediatric ALL patients who underwent PEG-asp-contained treatment on the 7th day after drug administration. Plasma L-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“… 3 Wu et al suggested, however, that glutamine level might assist the prevention of anaphylaxis-related AEs. 1 It is remarkable that these authors did find glutamine depletion, how could this phenomenon be explained? What was the role and the influence of day 7 post-infusion measurement on the glutamine level in this clinical study?…”
Section: Dear Editormentioning
confidence: 98%
See 3 more Smart Citations
“… 3 Wu et al suggested, however, that glutamine level might assist the prevention of anaphylaxis-related AEs. 1 It is remarkable that these authors did find glutamine depletion, how could this phenomenon be explained? What was the role and the influence of day 7 post-infusion measurement on the glutamine level in this clinical study?…”
Section: Dear Editormentioning
confidence: 98%
“…I have read with great interest the publication by Wu et al 1 In the context of the Chinese Children's Cancer Group (CCCG)-ALL-2015 protocol, they studied the plasma L-asp activity/anti-L-asp antibody/asparagine/glutamine levels of 91 pediatric ALL patients who underwent PEG-asp-contained treatment on the seventh day after drug administration. Very recently, this CCCG-ALL-2015 protocol was used in an open-label, multicenter, randomized, phase 3, non-inferiority trial which involved twenty major medical centers across China.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainably monitoring of L-asp activity would be decided by physicians according to patients’ individual condition, but not the way reported in this study. In addition, as mentioned in the Discussion Section, 3 the sustainably monitoring of L-asp activity, anti-L-asp antibody, Asn and Gln levels at multiple time points is still proceeding now.…”
mentioning
confidence: 99%